Effect of Time Delay of Support Propagation in Equations of Thin Films - Taranets, R. M.; Shishkov, A. E. (Ukrains’kyi Matematychnyi Zhurnal, 2003)
We prove the existence of the effect of time delay of propagation of the support of “strong” solutions of the Cauchy problem for an equation of thin films and establish exact conditions on the behavior of an initial function near the free boundary that guarantee the appearance of this effect.